Property Valuation Practices among Estate Surveying and Valuation Firms in Enugu Metropolis - Ifeanacho, K. P.; Nnamani, O. C.; Egbo, P. N.; Ani, I. E. (International Journal of Real Estate, 2025)
This study examines property valuation practices among Estate Surveying and Valuation firms in Enugu Metropolis, Nigeria. Data were obtained through structured questionnaires administered to forty registered firms, all of which were retrieved and analysed using descriptive statistics. The results show that valuation practice in Enugu is dominated by traditional methods such as the Depreciated Replacement Cost, Investment/Income Capitalisation, and Direct Market Comparison methods, while the use of modern approaches like the Discounted Cash Flow analysis is minimal. Most firms rely on intuition rather than empirical data in determining yields and outgoings, with percentage deductions from gross rent commonly applied. Although all firms comply with the standard deduction of outgoings from gross rent, inconsistencies remain in the components included. The study concludes that valuation practice in Enugu is largely experience-driven and lacks analytical depth. It recommends enhanced access to market data, continuous professional training, and adoption of modern valuation techniques to improve accuracy and consistency.
Keywords: Property valuation; Estate surveying practice; Valuation methods; Real estate market; Enugu metropolis